Alpha oscillatory dysregulation: mapping EEG oscillatory in suicidal depression - Zhao, Yue; Guo, Yuanyuan; Wu, Dongpeng; Zhang, Jiahua; Zheng, Shuang; Xie, Wen; Wang, Kai; Tian, Yanghua (Frontiers in Human Neuroscience, 2025)
BackgroundDepression is a common mood disorder that can lead to suicide in severe cases. The aim of this study was to explore the characteristics of electrical activity in different brain regions in depressive patients with suicidal ideation (DSI), and to provide new insights into the neural mechanisms of suicidal ideation.Methods21 DSI, 18 depressive patients without suicidal ideation (DNSI), and 20 demographically matched healthy controls (HC) were included in the study. Differences in EEG power spectral density (PSD), frontal alpha asymmetry (FAA), and functional connectivity (FC) were computationally compared among the three groups to assess the differences in these EEG metrics between the different groups.ResultsEEG analysis showed a significant increase in alpha-band PSD and a significant decrease in FAA in DSI compared to DNSI (p < 0.05). Compared with HC, DSI exhibited a significant increase in alpha-band FC between frontal-central and parietal-central regions (p < 0.05). Furthermore, in DSI, alpha-band FC between frontal and central regions was significantly and positively correlated with both severity (rho = 0.508, p = 0.038) and intensity (rho = 0.544, p = 0.024) of suicidal ideation.ConclusionThis study found significant alterations in the EEG alpha band in DSI compared to DNSI and HC. alpha band alterations may be a potential biomarker of suicide risk in depression. These findings contribute to further understanding of the neural mechanisms of DSI.